BENTUK PARTISIPASI MASYARAKAT TERHADAP KEPARIWISATAAN DI KAMPUNG WISATA TAMANSARI YOGYAKARTA - Sagala, Afrilia Elizabet; Nuryanti, Wiendu (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2019)
The 2015-2025 RIPPARDA stipulated in PP No.3 of 2015, Article 20 mentions the classification of historical and cultural tourism development objects, namely Tamansari. The development of tourism in Tamansari village is closely related to community participation. The research uses mixed methods, by combining two forms of approaches namely qualitative and quantitative in analyzing data and displaying data. The results showed (1) the development of tourism in Tamansari village was inseparable from community participation and the encouragement of the Tamansari Village organization in stimulating the activeness of the community, while the activist promoters were from community organizations. (2) the community of Tamansari Village participated with the percentage of ideas (100%), energy (100%), property (100%), skills (100%), and social (41%), with the results of the average form of cross tabulation participation in tourism namely: Attractions (48.2%), Amenities (30.2%), and Accessibility (16.3%), can be identified forms of skills participation in an attraction is a major influence (3) factors that influence participation, namely internal factors 72% and 75 , 63% of external factors affecting the community of Tamansari tourism village in participating. The dominant external factor affecting society is leadership and organization.